Maximising performance in hot environments a problem-based learning approach - Tyler, Christopher J. (Routledge, 2019)
Ensuring high levels of performance and safety in hot climates is a key consideration for sport scientists and coaches. Maximising Performance in Hot Environments is the first book with a project-based approach to focus solely on exercise in this common climatic condition, providing students and coaches with a clear and concise introduction to working with athletes in the heat. Rigorous in its physiological underpinnings, the book adopts a problem-based learning approach, encouraging students to engage with the science and apply it to practical, real-world scenarios. Posing questions such as 'how should athletes be monitored in high temperatures", "what are the ideal conditions for setting a world record in a 10,000m race", and "what specific considerations should be made when working with masters athletes", the book covers all key topics, including: the basics of human thermoregulation; the effect of high temperatures on performance; heat acclimation and acclimatisation; cooling; hydration; preventing heat-related illness and injury. Offering pedagogical features throughout to further enhance student learning, this is a truly innovative and unique resource. It is crucial reading for any student taking classes in environmental physiology, important applied reading for any exercise physiology students, and a vital companion for any sport scientist or coach working with athletes in high temperatures